Effect of Leadership and Distributive Justice on Turnover Intention with Workload as Intervening Variable, Study on PT XYZ - Sukarwati Sukarwati; Ahmad Badawi Saluy; Abdul Bari; Novawiguna Novawiguna (Dinasti International Journal of Education Management And Social Science, 2022)
This study aims to determine and analyze the influence of leadership and the effect of distributive justice on turnover intention, the influence of leadership and the influence of distributive justice to the workload at PT XYZ. In this case, the workload in this study be the intervening variable. This study uses a quantitative descriptive method with causal relationship approach. The process of collecting primary data is done through a questionnaire technique directly to 100 respondents based on Slovin sampling. While data analysis using Structural Equation Model (SEM) with SmartPLS (Partial Least Square) 3.0. Results of data analysis shows that: (i) high and low levels of leadership in the company, will not affect employee turnover intention, (ii) high distributive justice in the company, then will reduce the level of employee turnover intention, (iii) the perceived high workload employees, it will affect employee turnover intention, (iv) low workload, no will affect distributive justice in decreasing the intensity of turnover intention in employees.